Comparative analysis of performance and mechanisms of flood inundation map generation using Height Above Nearest Drainage. (January 2023) - Li, Zhouyayan; Duque, Felipe Quintero; Grout, Trevor; Bates, Bradford; Demir, Ibrahim
Abstract: The National Water Center (NWC) implemented Height Above Nearest Drainage (HAND) for nationwide flood mapping in the continental United States. Although having a large coverage and high accuracy, the implementation (NWCH) relies heavily on the NHDPlus dataset which limits its potential to handle user defined datasets. Comparison of the NWCH model accuracy and computational performance against the original HAND is missing in the literature. This study evaluated the flood maps generated using NWCH and a web-based implementation of the original HAND (WBH). An in-depth sensitivity analysis was conducted for WBH. Results suggest that WBH can generate comparable inundation extent with few inputs in regions where the water depths from the synthetic and catchment rating curves are consistent. Multi-depth approaches help resolve underestimations of WBH. This study demonstrated the original HAND's efficacy in flood mapping and its potential for applications for fast predictions with acceptable accuracy with limited computational resources. Highlights: Comparison of the NWC's HAND (NWCH) and a web version of the original HAND (WBH). WBH can predict satisfying flood extent with much fewer data in some cases. In-depth analyses of factors that influence the accuracy of the WBH. Sensitivity analysis of WBH and methods to improve the performance of the model.